A new species of the genus Milesia Latreille (Diptera: Syrphidae) from Crete - Bot, Sander; Mengual, Ximo; van Steenis, Jeroen; Skevington, Jeffrey H. (European Journal of Taxonomy, 2022)
Milesia cretica Bot & van Steenis sp. nov. is described from the Island of Crete, Greece. An identification key to all the European species of Milesia Latreille, 1804 is provided, together with DNA barcodes to distinguish the new species.